Effect of Pomegranate (Punica granatum) Peel Powder and Eucalyptus (Eucalyptus globulus) Leaves Powder on Growth Performance and Haemato-biochemical Study on Broilers - Choudhari, B. L.; Shende, K. A.; Meel, M. S.; Joshi, M.; Chavhan, D. M. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during August to October, 2024 at livestock farm complex, college of veterinary and animal science Navania, Udaipur, Rajasthan, India to evaluate the effect of dietary supplementation of pomegranate peel powder and eucalyptus leaves powder on growth performance and haemato-biochemical parameters of broilers for boosting poultry industry production. 120, day-old chicks were randomly assigned into four dietary treatment groups consisting of 30 chicks in each. The C group fed basal diet only, while T1 fed basal diet+eucalyptus leaves powder @ 0.5%, T2 fed basal diet+pomegranate peel powder @ 0.5% and T3 fed basal diet+combination of both powder @ 0.5%. Highest body weight was observed in T2 group which was comparable to T1 group and lowest body weight was observed in control group. Highly significant (p<0.01) effect on body weight gain, daily weight gain and performance index were noticed in T2 group supplemented with pomegranate peel powder which was comparable to T1 group and lowest was observed in Control group supplemented with basal diet. Lowest feed conversion ratio was observed in T2 group which was comparable with T1 and T3 group and highest feed conversion ratio was observed in control group. Significant effect was found in cholesterol and triglyceride level in T2 group as compared to control group. Significant increase in WBC was observed in T2 group which showed non-significant difference with T1 and T3 group. It can be concluded that supplementing broiler diet with pomegranate peel powder @ 0.5% could be beneficial for improving broiler chick growth performance.